A questionnaire-based study on the knowledge, attitude, and the practice of ecopharmacology among the healthcare professionals in Amaltas Medical College and Hospital, Dewas, Madhya Pradesh - Bhadoriya, Sandeep S.; Wadagbalkar, Prashant (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Ecopharmacology which deals with the health hazards posed by discarded or used medicinal products in the environment, is a globally emerging issue. There are guidelines for pharmaceutical waste management (like GMP and FDA guidelines) for the manufacturing units, pharmacists and consumers. However, it is uncertain whether consumers are aware of it. Before beginning the process of creating awareness, it is first necessary to assess the existing knowledge of the issue in the community. This study was planned to assess the knowledge, attitude and practice (KAP) of ecopharmacology in the medical personnel and students in our institute. Methods: It was a questionnaire based cross-sectional observational study. Study population included MBBS students, nursing students and resident doctors. Total 500 consenting participants were enrolled and subjected to a structured KAP questionnaire and data was expressed in percentage. Questionnaire consisted of 20 questions out of which 3 were open ended and remaining closed ended. Results: Present study result showed that 73% respondents had heard of term ecopharmacology and majority (98%) felt that it was their responsibility to protect environment from pharmaceutical waste. Responses from 83% of participants indicated that they were worried about the excess medicines at their homes. 87% of participants threw it in garbage bin, but (58%) were unsure whether their drug disposing method was safe and 25% knew it was unsafe. Most respondents (94%) felt that there should be guidelines for safe disposal of expired/unused drug and were enthusiastic about participating in campaign for this issue. Medical personnel also suggested some solutions to deal with this problem. Conclusions: Awareness and concern regarding the problem is high however in absence of knowledge of methods of safe disposal of unused drug, it is not transforming into safe disposal practices.